AB0281 A new risk factor in turkish children with enthesis related arthritis. (23rd January 2014) - Kara Eroglu, F.; Akkus, K.; Ozcakar, L.; Topaloglu, R.; Ozaltin, F.; Ozen, S.
Abstract : Background: Enthesis related arthritis (ERA) is a subtype of juvenile idiopathic arthritis, strongly associated with HLA B27. Objectives: We aimed to present the clinical, laboratory and radiological features of Turkish children with ERA. Methods: This is a single center, prospective study evaluating the clinical, laboratory and radiological features of 53 children (49 boys, 4 girls) fullfilling the ILAR criteria. HLA B27 was studied in all patients. MEFV mutation was studied in those negative for HLA B27 and in those with clinical features of FMF. Results: Male to female ratio was 12, 2, mean age at diagnosis was 12, 7±2, 3 years. The most frequently affected joint was the knee (%56) and all patients had an oligoarticular type of onset. Clinical examination revealed enthesitis in %49 of patients and an additonal %12 was described by ultrasonography, although they had no obvious symptoms. HLA B27 was positive in %75 of the patients. MEFV mutation was positive in %75 of the patients who were negative for HLA B27. With NSAIDs and sulphasalazine %73 of the patients achieved remission, antiTNF treatment was given for those who were non-responsive. Conclusions: Certain clinical features differ in Turkish ERA patients. In populations with high carrier rates for MEFV mutations, mutations in the pyrin protein is one of genetic risk factors for ERA, especially in those who lack the HLA B27 association. References: Jousse-Joulin S, Breton S, Cangemi C, Fenoll B, Bressolette L, de Parscau L, Saraux A, Devauchelle-Pensec V. Ultrasonography for detecting enthesitis in juvenile idiopathic arthritis. Arthritis Care Res (Hoboken). 2011 Jun;63(6):849-55. doi: 10.1002/acr.20444. Demirkaya E, Ozen S, Bilginer Y, Ayaz NA, Makay BB, Unsal E, Erguven M, Poyrazoglu H, Kasapcopur O, Gok F, Akman S, Balat A, Cavkaytar O, Kaya B, Duzova A, Ozaltin F, Topaloglu R, Besbas N, Bakkaloglu A, Arisoy N, Ozdogan H, Bakkaloglu S, Turker T. The distribution of juvenile idiopathic arthritis in the eastern Mediterranean: results from the registry of the Turkish Paediatric Rheumatology Association. Clin Exp Rheumatol. 2011 Jan-Feb;29(1):111-6. Disclosure of Interest: None Declared